Cancer outcomes research—a European challenge: measures of the cancer burden. Issue 12 (22nd June 2021) - Kalager, Mette; Adami, Hans‐Olov; Lagergren, Pernilla; Steindorf, Karen; Dickman, Paul W.
Abstract : In a mission that aims to improve cancer control throughout Europe, the European Academy of Cancer Sciences has defined two key indicators of progress: within one to two decades, overall cancer‐specific 10‐year survival should reach 75%, and in each country, overall cancer mortality rates should be convincingly declining. To lay the ground for assessment of progress and to promote cancer outcomes research in general, we have reviewed the most common population‐based measures of the cancer burden. We emphasize the complexities and complementary approaches to measure cancer survival and the novel opportunities for improved assessment of quality of life. We propose that: incidence and mortality rates are standardized to the European population; net survival is used as the measure of prognosis but with proper adjustments for confounding when temporal trends in overall cancer survival are assessed; and cancer‐specific quality of life is measured by a combination of existing questionnaires and utilizes emerging communication technologies. We conclude that all measures are important and that a meaningful interpretation also requires a deep understanding of the larger clinical and public health context. Abstract : This review defines the many measures used to quantify the burden of cancer, their pros, cons, and utility for different purposes. Recommendations are provided for the most informative measures and the methodologic challenges that need accommodation in assessing the Academy's goals. The needs and opportunities for development of and standardization of cancer‐specific quality of life assessments is also emphasized.